2021
DOI: 10.1038/s41586-021-04120-y
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and efficacy of          heterologous ChAdOx1–BNT162b2 vaccination

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

25
170
2
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(199 citation statements)
references
References 31 publications
25
170
2
2
Order By: Relevance
“…Yet, this observation is in agreement with other studies 19 , 21 , 44 and suggests that ChAdOx1 nCoV-19 / BNT162b2 prime-boost vaccination elicits particularly potent immune responses. 17 , 18 , 45 As reported for homologous vaccinations, 46 titres also decrease over time after heterologous vaccination. However, they remained high for three months post boost suggesting robust durable protection.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Yet, this observation is in agreement with other studies 19 , 21 , 44 and suggests that ChAdOx1 nCoV-19 / BNT162b2 prime-boost vaccination elicits particularly potent immune responses. 17 , 18 , 45 As reported for homologous vaccinations, 46 titres also decrease over time after heterologous vaccination. However, they remained high for three months post boost suggesting robust durable protection.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies addressing heterologous vaccinations indicated that the Delta variant is equally sensitive to neutralization as Alpha. 22 , 23 , 45 We observed that in correlation with the IgM/IgG titres, neutralizing titres against Delta are decreasing over the course of 13-17 weeks but remain detectable in all analysed sera at the latest time points. This confirms a good prediction by IgM/IgG titres and indicates durable protection from the most prevalent Delta variant.…”
Section: Discussionmentioning
confidence: 63%
“… 1 , 2 , 3 A booster vaccination (third dose of vaccine) has been proposed and initiated in many countries; and a prime-boost sequential immunisation approach is thought to be beneficial. 4 …”
mentioning
confidence: 99%
“…Several studies have addressed the efficacy and safety of this practice in the battle against SARS-CoV-2 and its variants. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 Adding to this evidence base, an Article in The Lancet by Arabella Stuart and colleagues reports the findings of the Com-COV2 Study Group, a multicentre survey network of nine institutions in the UK. 10 …”
mentioning
confidence: 99%
“…Although there are just a few randomised clinical trials in the literature involving heterologous vaccination schedules, many observational studies support the value of this approach, including studies of the ChAd/BNT, BNT/ChAd, ChAd/m1273, Ad26/Ad5, ChAd/BBV152, Coronavac/ChAd, Coronavac/Convidecia, and Ad26/BNT schedules. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 The baculovirus-derived NVX vaccine has been submitted to WHO for emergency use and its safety and efficacy have been documented, but randomised clinical trials are limited in number. 11 , 12 The NVX vaccine is produced in the baculovirus–insect cell system using the Wuhan sequence containing two prolines that stabilise trimer formation.…”
mentioning
confidence: 99%